Study to identify dietary factors and life style patterns responsible for gall stones among north Karnataka patients - Aravind, K; Suhas, Kalghatgi; Kulkarni, Mukund; T, Vipin; Kamat, Vijay (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Introduction: Gall stone disease is common problem in Indian subcontinent. Cholelithiasis has increasingly become a major cause of morbidity, leading to hospital admission and surgery in the developing world. There has also been a remarkable shift in the trend of gall-stone disease from middle aged, fertile, fat females to young asthenic females in their twenties. Material and methods: Descriptive analytic design study was conducted using questionnaire to collect required data. The study focused on the assessing risk factors of cholelithiasisamongst patients admitted for cholecystectomy. Cases (n = 39) from all age groups and both sexes with sonographically proven gallstones were included. Age- and sex-matched controls (n = 40) were chosen from among ward inmates admitted for other reasons. Univariate and multivariate logistic regression analyses were performed for selected sociodemographic, dietary, and lifestyle-related variables. Results: Out of the 79 subjects, 39 were cases and remaining 40 were controls. The mean age of 45.56 years was slightly higher in cases, as compared to 40.20 in controls in which females are more than males.The proportion of smoking participants at cases were 10.3% and the proportion was 5.0% at controls. The proportion of alcohol participants at cases were 10.3% and controls were 7.5% in the study population. The proportion of tobacco intake participants were 28.2% at cases and 32.5% at controls. The mean BMI at cases was 22.54 and the mean BMI was 20.32 at controls which was statistically significant with a P value 0.02. The mean WH ratio was 1.34 at cases and 0.81 at controls .The mean oil intake per month at cases were 650.79±346.48 and 617.5±285.0 at controls. The mean salt intake per month at cases and controls were 10.61±5.28 and 13.77±7.78 respectively. The mean non veg intake per month at cases were 4.20±6.53 and 1.89±2.14 at controls. Conclusion: Gallstone disease is frequent among females and elderly males. Significant predictor variables are abdominal adiposity, inadequate physical activity, and high intake of saturated fats; thus representing high risk lifestyles and yet amenable to primary prevention.